2014
DOI: 10.1016/j.colsurfb.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laminin adsorption on nanowires compared to flat surfaces

Abstract: Semiconductor nanowires are widely used to interface living cells, and numerous nanowire-based devices have been developed to manipulate or sense cell behavior. We have, however, little knowledge on the nature of the cell-nanowire interface. Laminin is an extracellular matrix protein promoting cell attachment and growth. Here, we used a method based on fluorescence microscopy and measured the relative amount of laminin adsorbed on nanowires compared to flat surfaces. The amount of adsorbed laminin per surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Experimental studies of Hammarin et al showed that the amount of adsorbed laminin per surface area is up to four times higher on 55 nm diameter gallium phosphide nanowires compared to the flat gallium phosphate surface. [67] Roach et al presented a systematic evaluation of protein response, in terms of conformation, to surface curvature. [51] They showed that a high surface curvature of silica particles with radii less than 30 nm promotes the native-like conformation of globular in shape albumin, in sharp contrast to rod-like fibrinogen, which becomes www.advancedsciencenews.com www.advhealthmat.de denatured to a greater extent.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…Experimental studies of Hammarin et al showed that the amount of adsorbed laminin per surface area is up to four times higher on 55 nm diameter gallium phosphide nanowires compared to the flat gallium phosphate surface. [67] Roach et al presented a systematic evaluation of protein response, in terms of conformation, to surface curvature. [51] They showed that a high surface curvature of silica particles with radii less than 30 nm promotes the native-like conformation of globular in shape albumin, in sharp contrast to rod-like fibrinogen, which becomes www.advancedsciencenews.com www.advhealthmat.de denatured to a greater extent.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…The effects of nanowires on the cell membrane are not well understood either and seem to depend on cell type, nanowire density, interaction time span, and position of the nanowires with respect to the cell 28 29 30 31 . Nanowires have been shown to promote neuronal adhesion and axonal growth 1 17 32 33 34 , which has recently been attributed to an enhanced laminin adsorption on nanowires caused by curvature effects 35 . The presence of nanowires has also been shown to increase the number of cells in the S phase of the cell cycle and to up-regulate focal adhesion formation 36 .…”
mentioning
confidence: 99%
“…Gallium phosphide as multimodel nanowire employed for different geometries such as rod and cone photoreceptor, ganglion cells, and bipolar cells [56]. Also, the same structure coated with poly-L-ornithine showed that nanowires have significant potential on morphology, adhesion, and metabolism of cells in comparison to the flat surface [57,58].…”
Section: Structure and Overview Of Nanowiresmentioning
confidence: 99%